La política exterior de derechos humanos durante el sexenio de Andrés Manuel López Obrador - Anaya Muñoz, Alejandro; Garibay Villalba, Montserrat (El Colegio de México A.C., 2025)
This article provides a detailed account of Mexico’s foreign policy on human rights during the six-year term of Andrés Manuel López Obrador (AMLO). It examines both continuity and change relative to previous administrations, with particular attention to tensions between the principle of sovereignty and non-intervention, and the policy of openness to international scrutiny and monitoring. The analysis identifies continuity in key actions aimed at maintaining Mexico’s traditional openness, a defining feature of its human rights foreign policy since the beginning of the century. It also notes the persistence of “denial” behaviors—characteristic of a more “sovereigntist” foreign policy—that have been evident since the Peña Nieto administration. At the same time, the AMLO government introduced changes suggesting a growing preference for sovereignty and non-intervention as foundational principles of Mexico’s foreign policy on human rights. The article concludes that, in the overall balance between openness and sovereignty, the latter has continued to gain ground—though not to the point of entirely displacing the former.